2012
DOI: 10.4161/auto.19012
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy

Abstract: The role of autophagy in the response of human hepatocytes to oxidative stress remains unknown. Understanding this process may have important implications for the understanding of basic liver epithelial cell biology and the responses of hepatocytes during liver disease. To address this we isolated primary hepatocytes from human liver tissue and exposed them ex vivo to hypoxia and hypoxia-reoxygenation (H-R). We showed that oxidative stress increased hepatocyte autophagy in a reactive oxygen species (ROS) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 42 publications
0
47
0
Order By: Relevance
“…Therefore, the elimination of a few unstable and potentially dangerous mitochondria by autophagy preserves cellular integrity and maintains cellular homeostasis [39]. Recent studies have shown that autophagy plays a protective role against the mitochondrial dysfunction and apoptosis induced by oxidative stress in hepatocytes [40,42]. Our data revealed that Baf.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Therefore, the elimination of a few unstable and potentially dangerous mitochondria by autophagy preserves cellular integrity and maintains cellular homeostasis [39]. Recent studies have shown that autophagy plays a protective role against the mitochondrial dysfunction and apoptosis induced by oxidative stress in hepatocytes [40,42]. Our data revealed that Baf.…”
Section: Discussionmentioning
confidence: 59%
“…Autophagy is a lysosome-mediated degradation process that regulates the turnover of long-lived proteins and eliminates dysfunctional organelles, including mitochondria, to preserve basal cellular and tissue homeostasis [5,39,40]. The autophagy pathway begins with the formation of double-membrane vesicles also known as autophagosomes, and LC3-II is a representative protein component of the autophagosomal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Damaged organelles participating in ROS generation, including mitochondria, are sequestrated and removed by the autophagic process, and autophagy plays a role in suppression of ROS generation and subsequent apoptosis [63]. Autophagy prevents hepatocyte apoptosis or necrosis under conditions of hypoxia-induced oxidative stress [54,56,64,65]. Considering these facts, it seems that the formation of mitochondrial autophagosomes in hepatocytes during warm ischemia suggested that the autophagy system plays a role in protecting hepatocytes from hypoxic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Bhogal et al showed that inhibition of autophagy using 3-methyladenine increases apoptosis in primary human hepatocytes under oxidative stress (56). More recently, work by Yun et al suggests that there is an impaired autophagy response after hepatic I/R, where pharmacologic inhibition of autophagy further exacerbates injury (57).…”
Section: Discussionmentioning
confidence: 99%